Pamana [videorecording] - Cuaresma, Joe Fernandez; Iglesias, Roy C.; Ongkeko, Ellen; Zialcita, Fernando N. (NCCA, 1995)
A tele-movie on ancestral houses and their importance and significance in Philippine culture. Features well-known actors and actresses.